1991
DOI: 10.1093/jn/121.4.445
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Food Folates and Evaluation of Food Matrix Effects with a Rat Bioassay

Abstract: Folate bioavailability of beef liver, lima beans, peas, spinach, mushrooms, collards, orange juice and wheat germ was estimated with a protocol of folate depletion-repletion using growth and liver, serum and erythrocyte folate of weanling male rats. Diets with 125, 250 and 375 micrograms folic acid/kg were standards. Individual foods were incorporated into a folate-free amino acid-based diet alone (250 micrograms folate/kg diet from food) or mixed with folic acid (125 micrograms folate from food + 125 microgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…This value is almost of the same magnitude as that generally found in some vegetables, higher than that of fruits (3–23 μg/100 g) (FAO 1972) and lower than in other wild mushrooms (1,222–1,412 μg/100 g dry weight) (Bano and Rajarathnam 1988). Fortunately, folic acid bioavailability in mushrooms is good compared to some vegetables, such as peas and spinach (Clifford et al 1991). …”
Section: Discussionmentioning
confidence: 99%
“…This value is almost of the same magnitude as that generally found in some vegetables, higher than that of fruits (3–23 μg/100 g) (FAO 1972) and lower than in other wild mushrooms (1,222–1,412 μg/100 g dry weight) (Bano and Rajarathnam 1988). Fortunately, folic acid bioavailability in mushrooms is good compared to some vegetables, such as peas and spinach (Clifford et al 1991). …”
Section: Discussionmentioning
confidence: 99%
“…Mushrooms contain moderately high amounts of folates at concentrations that are of the same magnitude as is generally found in vegetables. Furthermore, the bioavailability of folates is as good as that for folic acids (Clifford et al, 1991) with a content of 300-1412 μg/100 g. In addition to riboflavin, niacin and folates, cultivated mushrooms also contain small amounts of vitamin C and vitamin B1 and traces of vitamins B12 and D2 (Mattila et al, 2001).…”
Section: Vitaminsmentioning
confidence: 99%
“…Cliflord et al (88,89), using a rat bioassay model, reported folate bioavailability between 70 and 120% from food items like lyophilised orange juice, cooked lima beans, cooked leafy vegetables, wheat germ, eggs and mushrooms. These figures are higher than usually found in human studies based on similar food items.…”
Section: Human Folate Bioavailabilitymentioning
confidence: 99%